Tariffs, Income and Distribution - Kemp, Murray C. (Quarterly Journal of Economics, 1956)
I. Assumptions, 140. — II. Tariffs and employment under fixed exchanges, 141. — III. Tariffs and the distribution of income under fixed exchanges, 145. — IV. Tariffs, employment, and the distribution of income under flexible exchanges, 146. — V. Summary, 149.